Komik Digital Berbasis Scientific Method Sebagai Media Pembelajaran di Masa Pandemi COVID-19 - Very Hendra Saputra; Donaya Pasha (Jurnal Riset Teknologi dan Inovasi Pendidikan (Jartika), 2021)
Abstract: The aim of this research is to develop alternative media as a learning aid in the COVID-19 pandemic. The media developed is in the form of scientific method-based digital comics which adopt the steps from the 2013 Curriculum which includes observing, asking, trying, reasoning, and communicating. The developed comic media contains material about the circumference of a square for grade IV elementary schools. The comics developed were made with Adobe Photoshop software and comic life using the 4-D Research and Development (R&D) development method which includes defining, design, develop, disseminate. This research has succeeded in developing learning media in the form of digital comics in pdf and jpeg format that can be accessed via Android-based mobile phones. The results of the assessment of media experts and media learning material experts developed have Very Good quality (SB) with an ideal percentage of 85% media experts and 80% of material experts, as well as the technical quality aspects of students and parents of students 56.75% and 61.65 %. This shows that the media developed is suitable for use as a learning medium.